Perception Of Fish Farmers To Aquaculture Of Lele Dumbo (Clarias Gariepinus) In Pond Tarp In The Village Hangtuah In Perhentian Raja District Kampar Regency Of Riau Province - Pirmansyah, Bagus; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in June 2015 in the Village Hangtuah In Perhentian Raja District. This studyaims to determine how the fish farmers perception of the Catfish farming in the pond tarp after the floodingphenomenon. The method used in this research is survey method. To analyze the level of perception of fishfarmers used the Likert scale.Based on the results of the study public perception of individual fish farmers are in the good category inthe amount of 23 people (53.49%), while for the overall well being in either the category with a score of 3961.This suggests that the public perception of fish farmers either individually or overall are in good category thatthey agreed to continue these efforts.Key word: Dumbo Catfish, perception